Malaysian Design - Abd Rahman, Zainurul Aniza (Bloomsbury Publishing Inc, 2016)
Malaysia is a federation of thirteen states and three territories spread around the South China Sea, in the Malay Peninsula and the north and west of Borneo. Mostly populated by Malay, Chinese, Indian, and indigenous peoples, its history and culture, and therefore design, have been infused by multiple ethnic groups, religions, and beliefs.